Duration and frequency of non‐flow periods affect the abundance and diversity of stream meiofauna. (20th July 2020) - Majdi, Nabil; Colls, Miriam; Weiss, Linette; Acuña, Vicenç; Sabater, Sergi; Traunspurger, Walter
Abstract: Intermittent streams (IS) comprise a large proportion of the drainage network in many parts of the world. The non‐flow period of IS are known to impact stream biota because aquatic habitats dry out. However, less well understood are the relative effects of the temporal component of these drying events including their duration and frequency. Here, we characterised effects of temporal component of drying events on abundant and species‐rich meiofauna. The effects were assessed in 22 streams in the north‐eastern Iberian Peninsula. The duration and frequency of non‐flow events was characterized over a period of 250 days prior to sampling the sediment‐dwelling meiofauna in riffle zones that completely dried out. Overall, meiofauna abundances were amongst the highest ever reported for streambeds. Most meiofaunal taxa correlated positively with the frequency of drying events and correlated positively with the length of dry periods recorded shortly before sampling, suggesting that the community was able to recover quickly. Tardigrades were the only group to correlate positively with the longest dry periods, suggesting that they had the best resilience capabilities in streams that had experienced the longest droughts. On average, nematodes made up half of the meiofauna. We identified a total of 113 different nematode species. The nematode community was more taxonomically diverse in IS, with a smaller proportion of bacterivores and a higher proportion of fungivore species such as Filenchus vulgaris . Thereby resembling the trophic structure commonly observed in soil ecosystems. Our results show that most meiofauna were positively influenced by drying disturbance, that is being able to quickly recover after them. This suggests outstanding resilience capabilities, and points out meiofaunal organisms as key players for kick‐starting stream food webs and functions once flow returns.